1996
DOI: 10.1039/jm9960601211
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation reactions of UTeO5 and USeO5

Abstract: New intercalation compounds of the pseudo-layered oxides Uv'Te'v05 and UV'Se'V05 have been prepared and characterised At ambient temperatures products of the type AxUM05 (x < 1, A = Li, Na, H, NH,) are formed by both host oxides with minimal structural change Magnetic susceptibility measurements confirm that Uv species are formed on intercalation Several metal oxides, MO,, where M is a transition metal (or uranium) in a high oxidation state, have tunnelled or layered structures which undergo insertion or inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The bands at 400.90 and 430.49 cm −1 of UTeO 5 correspond to 392.23 cm −1 of UTeO 4 . The assignments of the vibrational modes of UTeO 5 (Dickens et al , 1996) are given along with the observed data.…”
Section: Resultsmentioning
confidence: 99%
“…The bands at 400.90 and 430.49 cm −1 of UTeO 5 correspond to 392.23 cm −1 of UTeO 4 . The assignments of the vibrational modes of UTeO 5 (Dickens et al , 1996) are given along with the observed data.…”
Section: Resultsmentioning
confidence: 99%